Use of Public Library Services by the Distance Learners of Bangalore University - G T, Mahesh; H, Dr. Adithya Kumari (DESIDOC Journal of Library & Information Technology, 2018)
The present paper investigates the distance students’ use of public libraries for their academic purposes and converse the public library as a alternate for instructive or University libraries. The current research study is based on a comprehensive survey of distance education students from Bangalore University. The data collection was carried out by personally distributing the questionnaire to the randomly selected students and the sample consists of students from both undergraduate and post graduate. It is found from the study that 1309 (90.60 %) distance learners who used public libraries during contact classes and 786 (54.4 %) of the respondents spent 0-1 h in the library. Majority of the distance learners i.e. 941 (65.10 %) responded effective for book borrowing services from the public libraries in seeking information, 1220 (84.40 %) opined effective for reference services. It is observed from the study that distance students have a tendency to look at libraries as a complete and do not make apparent difference between different types of libraries, expecting the entire system to be flawless. The paper lifts the significant executive inquiry and apprehension in relation to both the operation of public libraries and the service level given to diverse section of learning students. It is strongly recommended that library instruction programme should be organized by the public libraries for distance learners that create the responsiveness and use of library and information services effectively.